Long-term reduced functional capacity and quality of life in hospitalized COVID-19 patients - da Silveira, Anderson Donelli; Scolari, Fernando Luis; Saadi, Marina Petersen; Brahmbhatt, Darshan H.; Milani, Mauricio; Milani, Juliana Goulart Prata Oliveira; Junior, Gerson Cipriano; Sartor, Ivaine Tais Sauthier; Zavaglia, Gabriela Oliveira; Tonini, Maiko Luis; da Costa, Marcela Santos Correa; Scotta, Marcelo Comerlato; et al. (Frontiers in Medicine, 2024)
Background Persistent symptoms and exercise intolerance have been reported after COVID-19, even months after the acute disease. Although, the long-term impact on exercise capacity and health-related quality of life (HRQoL) is still unclear. Research question To assess the long-term functional capacity and HRQoL in patients hospitalized due to COVID-19. Study design and methods This is a prospective cohort study, conducted at two centers in Brazil, that included post-discharge COVID-19 patients and paired controls. The cohort was paired by age, sex, body mass index and comorbidities, using propensity score matching in a 1:3 ratio. Patients were eligible if signs or symptoms suggestive of COVID-19 and pulmonary involvement on chest computed tomography. All patients underwent cardiopulmonary exercise testing (CPET) and a HRQoL questionnaire (SF-36) 6 months after the COVID-19. The main outcome was the percentage of predicted peak oxygen consumption (ppVO2). Secondary outcomes included other CPET measures and HRQoL. Results The study sample comprised 47 post-discharge COVID-19 patients and 141 healthy controls. The mean age of COVID-19 patients was 54 ± 14 years, with 19 (40%) females, and a mean body mass index of 31 kg/m2 (SD, 6). The median follow-up was 7 months (IQR, 6.5–8.0) after hospital discharge. PpVO2 in COVID-19 patients was lower than in controls (83% vs. 95%, p = 0.002) with an effect size of 0.38 ([95%CI], 0.04–0.70). Mean peak VO2 (22 vs. 25 mL/kg/min, p = 0.04) and OUES (2,122 vs. 2,380, p = 0.027) were also reduced in the COVID-19 patients in comparison to controls. Dysfunctional breathing (DB) was present in 51%. HRQoL was significantly reduced in post COVID patients and positively correlated to peak exercise capacity. Interpretation Hospitalized COVID-19 patients presented, 7 months after discharge, with a reduction in functional capacity and HRQoL when compared to historical controls. HRQoL were reduced and correlated with the reduced peak VO2 in our population.